2000
DOI: 10.1063/1.125768
|View full text |Cite
|
Sign up to set email alerts
|

Solar-blind AlGaN photodiodes with very low cutoff wavelength

Abstract: Articles you may be interested inHigh quality AlGaN solar-blind Schottky photodiodes fabricated on AIN/sapphire template Appl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
90
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(90 citation statements)
references
References 10 publications
0
90
0
Order By: Relevance
“…6 Fig . 5 illustrates the plot of the responsivity versus dark current for the state-of-the-art solar blind (230-290 nm) UV detectors reported [4][5][6]8,[10][11]16,[30][31][32][33][34][35][36][37] for the devices based on Al x Ga 1-x N as well as on β-Ga 2 O 3 . The detectors reported in this work have excellent responsivity while maintaining a very low dark current for 230-240 nm range.…”
mentioning
confidence: 99%
“…6 Fig . 5 illustrates the plot of the responsivity versus dark current for the state-of-the-art solar blind (230-290 nm) UV detectors reported [4][5][6]8,[10][11]16,[30][31][32][33][34][35][36][37] for the devices based on Al x Ga 1-x N as well as on β-Ga 2 O 3 . The detectors reported in this work have excellent responsivity while maintaining a very low dark current for 230-240 nm range.…”
mentioning
confidence: 99%
“…The thick buffer layer was grown to reduce the defect density in the subsequent AlGaN layer. As the cut-off wavelength of Al x Ga 1-x N ternary material decreases for higher Al content, x ≥ 38% was needed to achieve a true solar-blind absorption spectrum [15]. MSM PD samples were fabricated using a four-step microwave compatible fabrication process in class-100 clean-room environment.…”
Section: Resultsmentioning
confidence: 99%
“…Cutoff wavelengths ( c ) as short as ϳ225 nm, an ultraviolet/ visible rejection over 5 orders of magnitude along with responsivities as high as 0.12 A/W at 232 nm were reported using a Al 0.7 Ga 0.3 N p -i -n detector structure. 6,11 Al 0.5 Ga 0.5 N MSM photodiodes with a noise equivalent power ͑NEP͒ as low as 30 fW at 280 nm and detectivity of 2.5 ϫ10 13 cm Hz 1/2 /W correspond to the best noise performance achieved for AlGaN-based solar-blind detectors. 15 Dark currents less than 2 pA at 30 V reverse bias and a 3 dB bandwidth of 100 MHz was reported for a Al 0.4 Ga 0.6 N MSM structure.…”
mentioning
confidence: 97%
“…2 Moreover, its intrinsic solar blindness ͑for x у0.38) and the ability of operation under harsh conditions ͑high-temperature and high power levels͒ due to its wide band gap makes Al x Ga 1Ϫx N-based photodetectors attractive for high-performance solar-blind detection applications. Several research groups have demonstrated successful solarblind operation with Al x Ga 1Ϫx N photodetectors using photoconductive, 3,4 p -i -n, [5][6][7][8][9][10][11][12][13][14] metal-semiconductormetal ͑MSM͒, 15,16 and Schottky [17][18][19][20] detector structures. Cutoff wavelengths ( c ) as short as ϳ225 nm, an ultraviolet/ visible rejection over 5 orders of magnitude along with responsivities as high as 0.12 A/W at 232 nm were reported using a Al 0.7 Ga 0.3 N p -i -n detector structure.…”
mentioning
confidence: 99%